The Meaning of Jihad in Social Life: A Study of Hadith Takhrij and SharÄ«'ah - Aulia, Najma (Journal of Takhrij Al-Hadith, 2024)
This study aims to discuss the hadith about the virtue of jihad. This research uses a qualitative approach by applying the descriptive-analytical method. The formal object of this research is the science of hadith, while the material object is the hadith about jihad in the Hadith narrated by Bukhari No. 2578. The results and discussion of this study indicate that the status of the hadith is shahih li dzatihi which meets the qualifications of maqbul for the practice of Islam. This study concludes that the Hadith narrated by Bukhari No. 2578 is relevant to be used as motivation, reminder, and guidance in implementing the meaning of jihad in social life.